Epidemiological evidence that indoor air pollution from cooking with solid fuels accelerates skin aging in Chinese women. Issue 2 (August 2015) - Li, Miaozhu; Vierkötter, Andrea; Schikowski, Tamara; Hüls, Anke; Ding, Anan; Matsui, Mary S.; Deng, Binwei; Ma, Chuan; Ren, Aiguo; Zhang, Juan; Tan, Jingze; Yang, Yajun; et al.
Highlights Indoor air pollution is a major public health challenge in China. Cooking with solid fuels is one main source of indoor air pollution in China. Cooking with solid fuels accelerates wrinkle rates in Chinese women. Corroborates known association between outdoor air pollution and skin aging. Indoor air pollution might be a further risk factor for skin aging.